2013
DOI: 10.1371/journal.pone.0074769
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide B Reduces LOX-1 Expression by Inhibiting Akt Phosphorylation and Increasing Sirt1 Expression in Oxidized LDL-Stimulated Human Umbilical Vein Endothelial Cells

Abstract: Oxidized low-density lipoprotein (ox-LDL) is an important risk factor in the development of atherosclerosis. LOX-1, a lectin-like receptor for ox-LDL, is present primarily on endothelial cells and upregulated by ox-LDL, tumor necrosis factor a, shear stress, and cytokines in atherosclerosis. Recent studies demonstrated that ginkgolide B, a platelet-activating factor receptor antagonist, has antiinflammatory and antioxidant effects on endothelial and nerve cells. The present study investigated the effects of gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 38 publications
1
20
1
1
Order By: Relevance
“…5). Consistently, increased SIRT1 and decreased Lox-1 expression levels have also been observed in oxLDL-stimulated human umbilical vein ECs exposed to ginkgolide B, an inhibitor of the platelet-activating factor with anti-inflammatory properties elicited via NF-jB inhibition and reduced ICAM-1 and MCP-1 expression (113). Interestingly, Lox-1 regulation of in vivo thrombus formation depends on the degree of activation by oxLDL.…”
Section: Sirt1 and Sirt6 In Cardiovascular Diseasesupporting
confidence: 60%
“…5). Consistently, increased SIRT1 and decreased Lox-1 expression levels have also been observed in oxLDL-stimulated human umbilical vein ECs exposed to ginkgolide B, an inhibitor of the platelet-activating factor with anti-inflammatory properties elicited via NF-jB inhibition and reduced ICAM-1 and MCP-1 expression (113). Interestingly, Lox-1 regulation of in vivo thrombus formation depends on the degree of activation by oxLDL.…”
Section: Sirt1 and Sirt6 In Cardiovascular Diseasesupporting
confidence: 60%
“…Previous studies reported that allicin protected cells against oxidative stress by inhibiting the generation of intracellular ROS [ 31 , 32 ]. Nrf2 is a redox-sensitive transcription factor that plays a key role in cellular antioxidant defense [ 33 ]. In the presence of oxidative stress, Nrf2 is rapidly degraded by the proteasome system, enters the nucleus, binds to antioxidant response element, and upregulates multiple antioxidant and detoxifying genes, such as HO-1 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic role of LOX-1 in atherosclerosis has been extensively elucidated. Silencing of LOX-1 by ginkgolide B in oxLDL stimulated endothelial cells led to inhibition ICAM-1 expression and Akt phosphorylation which results in a reduction of oxidative stress injury in endothelial cells [ 83 ]. In addition, knockdown of LOX-1 in mice fed with high cholesterol diet significantly reduced atherogenesis by sustaining endothelial function and inhibiting pro-inflammatory and pro-oxidants signals.…”
Section: Nrf2 and Macrophage Foam Cells Formationmentioning
confidence: 99%